Evolutionary learning in strategy-project systems : a PMI research monograph - Gardiner, Paul D.; Gardiner, Paul D.; Eltigani, Adil; Williams, T. M.; Kirkham, Richard J.; Ou, Lixiong; Calabrese, Antonio; Söderlund, Jonas (Project Management Institute, Inc., 2018)
What does a successful knowledge management practitioner do? Evolutionary Learning in Strategy-Project Systems explores the gap between the theory and practice of knowledge management in organizations and analyzes how learning happens and how knowledge is created. The authors take a practitioner-driven approach, one that unites organizational strategy with the learning of organizational lessons -- the kind of knowledge management that enhances project performance and ultimately business success. Through a survey of the literature and an analysis of original case-study research, Evolutionary Learning in Strategy-Project Systems develops a model of learning capability that proceeds exactly as its title implies, not as a line, but as a cycle -- from codifying individual knowledge and putting it into practice within a context that values social relationships and networks. The conclusions offered in this book build on the rethinking of project management literature in today's world -- creating a strategy-project learning model that not only improves current knowledge capabilities, but also develops new ones
Incluldes glossary (p. 275.
Keywords: Project management.; Knowledge management.; Organizational learning.; elektronické knihy; electronic books